2016
DOI: 10.1111/1460-6984.12288
|View full text |Cite
|
Sign up to set email alerts
|

Language development, delay and intervention-the views of parents from communities that speech and language therapy managers in England consider to be under-served

Abstract: The findings are discussed in relation to previous literature and the Developmental Niche Framework. Clinical implications include ideas about issues for SLTs to discuss with families and the need to recognize that parents may see themselves as competent facilitators of language. Suggestions are made for future research, including: expanded investigation of a wider range of under-served groups, an exploration of who parents consult when concerned about their child's language, and how key community figures advi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
(54 reference statements)
0
24
0
Order By: Relevance
“…In order to create mutual understanding about the parents’ and SLTs’ roles, SLTs should invest in talking more about parents’ central role during the initial consultation and during intervention (Marshall et al . , Goodhue et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to create mutual understanding about the parents’ and SLTs’ roles, SLTs should invest in talking more about parents’ central role during the initial consultation and during intervention (Marshall et al . , Goodhue et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Marshall et al . () found that parents did not express guilt or a sense that it was their fault. Parents need to be confident in their abilities in order to engage fully in therapy (Hibbard and Gilburt , Joseph‐Williams et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the perspectives of children regarding the services and care they receive were frequently provided by their parents, carers or indeed professionals (Roulstone & McLeod, ). This practice has been challenged by international policy (World Health Organization, ), and researchers and practitioners (Coad & Hambly, ; Horne et al, ; Marshall et al, ). More recently in the United Kingdom, professionals are now required to take account of children and young people's views (Gov.uk, ; Gov.uk, ).…”
Section: Introductionmentioning
confidence: 99%